Konsekwencje zjawiska powodzi dla funkcjonowania środowiska naturalnego - Grabowska, Monika (Consequences of Flooding for Natural Environment Functioning, 2005)
The natural environment characterizes complicated inner dependences and some kind of susceptibility to return to its balance. Sometimes areas which earlier were destructed could be reconstructed. This especially concerns floods. The article submits consequences of flooding for natural environment functioning. There a lot of possible negative influence of floods for natural environment. It is the challenge for ecology, soziology and present theory of economy (ecological economy).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 124-130